Implementation Of Work Ethic, Compensation, Discipline And Effect On Performance Lecturers And Educational Staff: Case study of STIE Widya Gama Lumajang - Jariah, Ainun (Jurnal Ilmu Manajemen Advantage, 2017)
Colleges as providers of educational services must be able to give the best service to the consumer in this case should be able to have the quality of human resources. How can it be expected to provide the best service to students if the human resources involved can not feel comfortable in working so could not provide the best performance for the college. The purpose of this study was to determine the effect of the work ethic, financial compensation, nonfinancial compensation, and work discipline on the performance of lecturers and Personnel in STIE Widya Gama Lumajang, either partially or simultaneously. Mechanical research by distributing questionnaires and the research method used is multiple linear regression method . The results that partial compensation of financial and work discipline that has an influence on the performance of lecturers and Personnel. While simultaneously work ethic, financial compensation, nonfinancial compensation, and work discipline affect the performance of lecturers and Personnel in STIE Widya Gama Lumajang. Performance can be explained by the variable work ethic, financial compensation, nonfinancial compensation, work discipline 64.4% while the remaining 35.6% performance is influenced by other variables not examined in this study.